Procurement of Materials and Components for Manufacturing Activity - Sulgan, Marian; Sosedova, Jarmila (Communications - Scientific Letters of the University of Zilina, 2014)
Contribution provides insight into various forms of procurement of material inputs in production companies in the Slovak Republic. Compares the traditional approach with modern systems and highlights the main features of each system with respect to logistics activities.
Keywords: material procurement; inbound logistics; purchase; Just-in-Time; Just-in Sequence